Earthquakes (A case study of Afghanistan) (Salam International Academic Journal, 2020)
According to widespread scientific beliefs, most earthquakes occur ‎when two pieces of the Earth's hard crust are placed one above the other ‎due to instantaneous motion, so that the extension of their surface ‎motion causes the earth to move or fail. This instantaneous motion ‎causes the release of strong energy and the production of large waves in ‎the earth's crust, which in a short time are scattered throughout the ‎earth's crust. The mentioned waves cause strong vibrations in the ‎surface of the earth, which is the basis or rule for the analysis and ‎stability of buildings against the force of earthquakes‏.‏Unfortunately, Afghanistan is in serious danger of earthquakes and ‎suffers a lot of damage and casualties from this area every year. ‎Afghanistan is located in the center of the Asian continent in the active ‎structure of the Himalayan Alpine Earthquake Belt, which has developed ‎over a large area due to the collision of tectonic plates between India, ‎Arabia and Europe-Asia.‎Earthquake risk should be given serious consideration when choosing a ‎site for construction and reconstruction of communities and facilities in ‎Afghanistan. The northeastern part of Badakhshan province is the ‎strongest earthquake zone in Afghanistan. Provinces such as ‎Badakhshan, Panjshir, Takhar, Kabul, Bamyan, Ghazni and Kandahar ‎have the strongest earthquakes‏.‏